Maternal exposure to urinary polycyclic aromatic hydrocarbons (PAH) in pregnancy and childhood asthma in a pooled multi-cohort study. (December 2022) - Loftus, Christine T.; Szpiro, Adam A.; Workman, Tomomi; Wallace, Erin R.; Hazlehurst, Marnie F.; Day, Drew B.; Ni, Yu; Carroll, Kecia N.; Adgent, Margaret A.; Moore, Paul E.; Barrett, Emily S; Nguyen, Ruby H.N.; et al.
Abstract: Background: Prenatal exposure to polycyclic aromatic hydrocarbons (PAH) may increase risk of pediatric asthma, but existing human studies are limited. Objectives: We estimated associations between gestational PAHs and pediatric asthma in a diverse US sample and evaluated effect modification by child sex, maternal asthma, and prenatal vitamin D status. Methods: We pooled two prospective pregnancy cohorts in the ECHO PATHWAYS Consortium, CANDLE and TIDES, for an analytic sample of N = 1296 mother–child dyads. Mono-hydroxylated PAH metabolites (OH-PAHs) were measured in mid-pregnancy urine. Mothers completed the International Study on Allergies and Asthma in Childhood survey at child age 4–6 years. Poisson regression with robust standard errors was used to estimate relative risk of current wheeze, current asthma, ever asthma, and strict asthma associated with each metabolite, adjusted for potential confounders. We used interaction models to assess effect modification. We explored associations between OH-PAH mixtures and outcomes using logistic weighted quantile sum regression augmented by a permutation test to control Type 1 errors. Results: The sociodemographically diverse sample spanned five cities. Mean (SD) child age at assessment was 4.4 (0.4) years. While there was little evidence that either individual OH-PAHs or mixtures were associated with outcomes, we observed effect modification by child sex for most pairs of OH-PAHs and outcomes, with adverse associations specific to females. For example, a 2-fold increase in 2-hydroxy-phenanthrene was associated with current asthma in females but not males (RRfemale  = 1.29 [95 % CI: 1.09, 1.52], RRmale  = 0.95 [95 % CI: 0.79, 1.13]; pinteraction  = 0.004). There was no consistent evidence of modification by vitamin D status or maternal asthma. Discussion: This analysis, the largest cohort study of gestational PAH exposure and childhood asthma to date, suggests adverse associations for females only. These preliminary findings are consistent with hypothesized endocrine disruption properties of PAHs, which may lead to sexually dimorphic effects.